2022
DOI: 10.1038/s41598-022-07526-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deleterious missense PRKCI variants on structural and functional dynamics of protein

Abstract: Protein kinase C iota (PKCɩ) is a novel protein containing 596 amino acids and is also a member of atypical kinase family. The role of PKCɩ has been explored in neurodegenerative diseases, neuroblastoma, ovarian and pancreatic cancers. Single nucleotide polymorphisms (SNPs) have not been studied in PKCɩ till date. The purpose of the current study is to scrutinize the deleterious missense variants in PKCɩ and determine the effect of these variants on stability and dynamics of the protein. The structure of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The structure of CTLA4 and its mutants were predicted via I-TASSER. The nsSNPs directly influence the structure and hence function of a protein therefore, the effect of nsSNPs on structure of CTLA4 was assessed 47 . It was observed that the predicted mutant structures of CTLA4 have significantly distinguished RMSD values than the wild type and may compromise the structural integrity of the protein 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The structure of CTLA4 and its mutants were predicted via I-TASSER. The nsSNPs directly influence the structure and hence function of a protein therefore, the effect of nsSNPs on structure of CTLA4 was assessed 47 . It was observed that the predicted mutant structures of CTLA4 have significantly distinguished RMSD values than the wild type and may compromise the structural integrity of the protein 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in 2022, different PKCι missense variants were evaluated for pathogenicity and potential for carcinogenesis [ 9 ]. Out of those variants, two were present in the PB1 domain were selected for this particular study because the function of the PB1 domain is essential for the interaction of PKCι with Par-6 during cellular polarity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, pathogenic variants of PKC (rs1199520604, rs1197750201) were also investigated for their association with breast cancer pathogenesis. The pathogenicity of these variants was determined in the previous study using several bioinformatics approaches (17). The outcomes of this study will facilitate the development of genetic marker that could facilitate in breast early diagnosis and prognosis and could reduce the risk of drug resistance development.…”
Section: Introductionmentioning
confidence: 92%
“…PKC is involved in several carcinogenic processes and its altered expression levels have been reported in various types of cancers (9,18,19). In our previous study, we have scrutinized deleterious polymorphic variants of PKC (17). Out of those, SNPs of the PB1 domain G34W (rs1199520604), and F66Y (rs1197750201) of PKC were selected for the assessment of association with breast cancer.…”
Section: Selection Of Gene and Variants For Arm's Pcrmentioning
confidence: 99%